Hyperfine structure and isotope shift of neutral and singly ionized europium by Fourier transform spectroscopy - Yaxin Wu; Huiting Ma; Yongfan Li; Lijun Zhang; Meina Liu; Yidan Geng; Zhenwen Dai (Results in Physics, 2023)
The magnetic dipole hyperfine structure (HFS) constants A of neutral and singly ionized europium (Eu I and Eu II) were determined using the emission spectra recorded by the Fourier transform spectrometer at the National Solar Observatory (NSO) at the Kitt Peak, USA. The HFS constants of 29 levels of Eu I and 15 levels of Eu II were determined, from which 22 results for Eu I and 8 results for Eu II are reported for the first time, as far as we know. The isotope shifts (ISs) of 30 transitions of Eu I and 19 transitions of Eu II were also determined, and the ISs of 22 transitions of Eu I and 8 transitions of Eu II are reported for the first time. This work increases the total number of levels with experimentally determined HFS constants A to 202 for Eu I and 24 for Eu II, and increases the number of transitions with known ISs to 359 for Eu I and 36 for Eu II.